A Study on Monetization (Tawatuq) from the perspective of Bank Negara Malaysia and AAOIFI Standards: Malaysian Practice - Abdurrahim, Muhammad Najib; Megat Laksana, Nan Noorhidayu; Abdul Aziz, Akhtarzaitie (IRAJ, 2018)
Through the commencement of Islamic Banking Act (IBA) on 1983, until the enactment of Islamic Financial Services Act (IFSA) on 2013, Islamic financial industry has shown its commitments towards the financial industry arld its stakeholders through the development of a distinctive products based on the various Islamic contracts such as Islamic hire purchase for vehicle and machine based on the concept of a contract of leasing ending with sale (al-Ijdrah Thumma al-Bay ), Islamic personal financing based on the concept of sell and buy back with arrangement (Bay' al-I'nah),Islamic house financing based on the concept of diminishing joint ventures (Musharakoh Mutandqi;ah) and others. On 28ft July 2005, the SharT'ah Advisory Council of National Bank Malaysia (SAC BNM) had resolved that financing and deposit product based on the concept of monetization (tawaruuq) is permissible. This resolution then has become ut alteraative way for the Islamic financial institutions to overcome the liquidity issue without relying on the controversial contract of sell and buy back with arrangement (Bay' al-'Inah) anymore. Monetization (tawarruq) is a process where a person buys a commodity with defened price, subsequently sells it on spot payment, usually with lower price to another party other than the first seller, with intention to obtain cash/liquidity. Thus, this study aims to discuss the role of National Bank Malaysia and Accounting and Auditing of Islamic Financial Institutions (AAOIFD Standard regarding the concept of monetization (tawarruq) in Malaysia. With regard to the methodology, this study will use both qualitative and quantitative methods. However, the qualitative method will become the main method for this study. The instrument of qualitative method is an interview session with the main stakeholders involved in the development of monetization (tawarruq) Standard. This study will contribute from the theoretical and practical perspective of monetization (tawarruq) operution an! application in Malaysia, argument and deliberation of monetization (tawarruq) not only from classical Islamic perspective, but also from modern application and discussion.